Pembiasaan Sikap Gotong Royong Melalui Program Kegiatan Kampus Mengajar Angkatan 3 di Sekolah Dasar - Suharjono, Gilang Eko Setyo (Jurnal Didaktika Pendidikan Dasar, 2025)
The current Indonesian education system refers to the Merdeka Curriculum, which emphasizes character building as reflected in the strengthening of the Pancasila student profile, which aims to improve the quality of education by shaping the character of students, one dimension of which is mutual cooperation. Teachers play an important role in fostering values of mutual care and concern among students, one of which is through the habit of mutual cooperation. This study aims to describe the cultivation of mutual cooperation attitudes among third-grade students through the implementation of the Kampus Mengajar Batch 3 program at SDN Gelang 06. This is a qualitative study using data collection techniques such as observation, interviews, and documentation. The data obtained from the field research were analyzed using descriptive qualitative methods. The results of this study indicate that the cultivation of a mutual cooperation attitude through the Kampus Mengajar Batch 3 program has a positive impact on third-grade students at SDN Gelang 06. Through program activities such as handicrafts, healthy Friday, inter-class competitions (class meetings) and group discussion learning applied to the students, changes in behavior reflecting mutual cooperation attitudes were demonstrated, such as concern for fellow students, cooperation, mutual assistance, sharing and creating harmony through mutual respect.